The Impact of Sustainable Finance on Economic Development - Bakoeva Gulbakhor (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
This article explores the growing importance of sustainable finance as a driver of long-term economic development. It analyzes how financial systems integrating environmental, social, and governance (ESG) principles contribute to economic resilience, social equity, and environmental protection. Drawing on evidence from both developed and emerging economies, the study highlights the role of green bonds, responsible banking, and public-private partnerships in accelerating sustainable growth. The paper concludes that sustainable finance not only supports environmental goals but also enhances financial stability and inclusive prosperity.